Ethnopharmacology and therapeutic potential of Anchusa strigosa: a comprehensive review - Chebaro, Ziad; Badran, Adnan; Maresca, Marc; Baydoun, Elias; Mesmar, Joelle Edward (Frontiers in Pharmacology, 2023)
Anchusa strigosa Banks and Sol. is a rough flowering plant of the Boraginaceae family native to Eastern Mediterranean region that is widely used in traditional herbal medicine, mainly for the treatment of wounds, abdominal pain, and arthritis, to name a few. This article aims to gather knowledge related to the medicinal properties of A. strigosa. Specifically, it summarizes its traditional uses and pharmacological activities in the treatment of various diseases. Moreover, its botanical, ecological, and phytochemical characteristics are also discussed. Research showed that this plant is rich in pyrrolizidine alkaloids, particularly in the leaves. Other bioactive metabolites identified in this plant include flavonoids, phenolic acids, triterpenes, organic acids, and volatile organic compounds. These phytochemicals are responsible for the reported pharmacological properties of A. strigosa, including antimicrobial, antioxidant, anticancer, anti-inflammatory, antiarthritic, gastric protective, antidiabetic, and pro-wound healing. This warrants further investigation into the molecular mechanism of action behind the observed effects to elucidate its therapeutic potential. Nevertheless, more research on this plant is needed to ensure its efficacy and safety.